1990
DOI: 10.1016/0735-1097(90)90290-6
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia and syncope as manifestations of partial epilepsy

Abstract: Although transient increases in heart rate typically occur, bradycardia has infrequently been noted in association with partial seizures. Five patients with temporal lobe epilepsy are described in whom sinus bradyarrhythmias and syncope were prominent manifestations of seizure activity. Partial improvement occurred in one of two patients in whom a permanent pacemaker was implanted before a diagnosis of epilepsy was established. Treatment with phenytoin or carbamazepine resulted in nearly complete resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…Ten of the 13 patients identified in this series had a diagnosis of epilepsy without a suspicion of a bradyarrhythmia, and the diagnosis would have been missed without simultaneous video-EEG/ECG monitoring. In two of our cases and in six ictal bradycardia patients in the literature, ictal bradycardia was diagnosed only after cardiac pacing failed to control symptoms in patients previously diagnosed with cardiogenic or vasovagal syncope based on ECG monitoring alone [4,6,7,11,16]. Prolonged ECG monitoring without EEG may mislead the physician, as the finding of bradycardia coincident with a logged clinical event during prolonged ECG monitoring may suggest a primary cardiogenic diagnosis [14].…”
Section: Discussionmentioning
confidence: 70%
“…Ten of the 13 patients identified in this series had a diagnosis of epilepsy without a suspicion of a bradyarrhythmia, and the diagnosis would have been missed without simultaneous video-EEG/ECG monitoring. In two of our cases and in six ictal bradycardia patients in the literature, ictal bradycardia was diagnosed only after cardiac pacing failed to control symptoms in patients previously diagnosed with cardiogenic or vasovagal syncope based on ECG monitoring alone [4,6,7,11,16]. Prolonged ECG monitoring without EEG may mislead the physician, as the finding of bradycardia coincident with a logged clinical event during prolonged ECG monitoring may suggest a primary cardiogenic diagnosis [14].…”
Section: Discussionmentioning
confidence: 70%
“…7-11 Earlier studies have found permanent pacing effective 7-9 or ineffective. 10, 11 Schuele et al reported similar changes in heart rate and duration of asystole during clinical events in patients presenting with ictal bradycardia/asystole versus neurally mediated reflex syncope, suggesting that both are mediated by a mechanism involving medullary reflex centers and a transient increase in vagal tone. 2 In multicenter randomized studies, permanent pacing was ineffective in patients presenting with neurally mediated reflex syncope.…”
Section: Images In Cardiovascular Medicine Syncope and Ictal Asystolementioning
confidence: 86%
“…The most commonly observed alteration in cardiac rhythm is tachycardia 33 . 35 , 36 , 41 –46 However, there have been an increasing number of reports of ictal bradycardia, some of which lead to sinus arrest or syncope 47 –55 . The ictal change in consciousness in patient 2 was not thought to be syncope due to bradycardia, but rather CPS because the blood pressure showed no notable decrease during the ictal periods.…”
Section: Discussionmentioning
confidence: 97%